(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present research has examined the relationship between the spiritual intelligence of the nursing staff in several hospitals in Darbhanga town and their caring behaviours. As a sample for the study, 320 nursing staff members were chosen by a purposive-cum-incidental strategy. There were nurses from both public and private institutions in the sample. The study’s objectives also included evaluating the impact of participants’ age and education on their capacity to show caring behaviour. The Personal Data Sheet, Caring Behaviour Scale, and Spiritual Intelligence Scale were employed in the study to collect the demographic data and gauge the participants’ levels of spiritual intelligence and caring behaviour, respectively. The 24 components that make up the Caring behaviour scale were created by Wu, Larrabee, and Putman (2006). By Kumar and Mehta (2011), the Spiritual Intelligence Scale (SSI) was developed.